Narrative of Puteri Santubong and Puteri Sejinjang in local politics: pragmatic analysis [Naratif Puteri Santubong dan Puteri Sejinjang mempertalikan politik tempatan: analisis pragmatik] - Daud, Muhammad Zaid; Subet, Mary Fatimah (Universiti Malaysia Sarawak, 2021)
This study aimed to analyze the implicatures (implicit meaning) in Sarawak Malay folk literature, “Puteri Santubong and Puteri Sejinjang” in local politics. The implicit meaning contained in the narrative was analysed using the Relevance Theory by Sperber and Wilson. The findings showed that explicatures such as “Puteri Santubong”, “Puteri Sejinjang”, “kisah lama, zaman mensia maya”, “penjaga”, “manis”, “anak dak dewa turun kayangan”, “bertenun kain”, “malam”, “menumbuk padi” and “siang” also contained implicatures that can be associated with the current context. This is in line with the role of folk literature, which is laden with the elements of subtle advice and satire so that society do not repeat the mistakes that occur in the narrative of Puteri Santubong and Puteri Sejinjang. In conclusion, by combining context, cognitive effects, and information processing effects, the implicit message in this narrative can be expanded based on local political conditions.